2016
DOI: 10.1093/nar/gkw066
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dual-color tracking of genomic loci by modified sgRNAs of the CRISPR/Cas9 system

Abstract: Visualization of chromosomal dynamics is important for understanding many fundamental intra-nuclear processes. Efficient and reliable live-cell multicolor labeling of chromosomal loci can realize this goal. However, the current methods are constrained mainly by insufficient labeling throughput, efficiency, flexibility as well as photostability. Here we have developed a new approach to realize dual-color chromosomal loci imaging based on a modified single-guide RNA (sgRNA) of the CRISPR/Cas9 system. The modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 56 publications
(49 reference statements)
6
137
1
8
Order By: Relevance
“…Thus, microscopy studies revealed major principles of nuclear architecture and provided evidence for a correlation between nuclear location and transcriptional output. With recent advances in superresolution microscopy (Lakadamyali and Cosma 2015) and novel sophisticated means to follow endogenous loci with high precision in living cells (Chen et al 2013;Saad et al 2014;Shao et al 2016), microscopy is expected to only become more important for nuclear organization research.…”
Section: Basic Principles Of Genome Organization Uncovered By Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, microscopy studies revealed major principles of nuclear architecture and provided evidence for a correlation between nuclear location and transcriptional output. With recent advances in superresolution microscopy (Lakadamyali and Cosma 2015) and novel sophisticated means to follow endogenous loci with high precision in living cells (Chen et al 2013;Saad et al 2014;Shao et al 2016), microscopy is expected to only become more important for nuclear organization research.…”
Section: Basic Principles Of Genome Organization Uncovered By Microscopymentioning
confidence: 99%
“…Nowadays, many more methods than integrating and tagging arrays of bacterial operator sequences (tetO and lacO) (Belmont and Straight 1998) are available for visualization. While some methods still require manipulation of the genomic sequence (Saad et al 2014), other novel methods employ fluorescent proteins fused to transcription activator-like effectors (TALEs) Miyanari et al 2013), dCas9 (Chen et al 2013), or even guide RNAs using aptamer sequences (Shao et al 2016). A different approach is the m 6 A-Tracer that detects the adenine-6 methylation deposited by DNA adenine methyltransferase identification (DamID) (Kind et al 2013).…”
Section: Future Perspectivementioning
confidence: 99%
“…For this, dCas9 is fused with a fluorescent protein, either as a part of a fusion protein (Chen et al, 2013; Anton et al, 2014; Ma et al, 2015; Anton et al, 2016; Chen et al, 2016) or through an RNA scaffold (McDonald et al, 2016; Shao et al, 2016) (Fig. 1E).…”
Section: Cas9-mediated Chromatin Visualizationmentioning
confidence: 99%
“…Apart from genome editing, catalytically dead Cas9 (dCas9) has been widely used as a programmable DNA-binding protein, enabling in situ imagining of genomic loci (Shao et al, 2016) and precise control of transcription through repression or activation (Wang et al, 2016). Recent studies demonstrated that DNase-dead Cas12a can also be used for gene regulation in bacteria and plants (Tang et al, 2017; Zhang et al, 2017), suggesting that a wider range of applications will also be enabled by dCas12a.…”
Section: Applications Based On Type V and Vi Systemsmentioning
confidence: 99%